2009
DOI: 10.1051/0004-6361/200912446
|View full text |Cite
|
Sign up to set email alerts
|

Photometric calibration of the Supernova Legacy Survey fields

Abstract: Aims. We present the photometric calibration of the Supernova Legacy Survey (SNLS) fields. The SNLS aims at measuring the distances to SNe Ia at (0.3 < z < 1) using MegaCam, the 1 deg 2 imager on the Canada-France-Hawaii Telescope (CFHT). The uncertainty affecting the photometric calibration of the survey dominates the systematic uncertainty of the key measurement of the survey, namely the dark energy equation of state. The photometric calibration of the SNLS requires obtaining a uniform response across the im… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
159
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 123 publications
(160 citation statements)
references
References 53 publications
1
159
0
Order By: Relevance
“…The SNLS "combined" compilation consists of 123 SNe Ia at low redshifts, 242 SNe Ia from the three-year Supernova Legacy Survey (SNLS; see Regnault et al 2009;Guy et al 2010;Conley et al 2011), 93 intermediate redshift SNe Ia from the Sloan Digital Sky Survey (SDSS; Holtzman et al 2008;Kessler et al 2009) and 14 objects at high redshift observed with (HST; Riess et al 2007).…”
Section: The Snls Compilationmentioning
confidence: 99%
“…The SNLS "combined" compilation consists of 123 SNe Ia at low redshifts, 242 SNe Ia from the three-year Supernova Legacy Survey (SNLS; see Regnault et al 2009;Guy et al 2010;Conley et al 2011), 93 intermediate redshift SNe Ia from the Sloan Digital Sky Survey (SDSS; Holtzman et al 2008;Kessler et al 2009) and 14 objects at high redshift observed with (HST; Riess et al 2007).…”
Section: The Snls Compilationmentioning
confidence: 99%
“…-A new photometric calibration has been applied to the T0007 release. While the previous releases and the CFHTLenS release rely on Landolt standard stars (see Erben et al 2013), T0007 is based on the spectrophotometric tertiary standards from the Super Novae Legacy Survey (SNLS; see the procedure described in Regnault et al 2009). In brief, each tile of the CFHTLS-Wide is re-observed (with short exposures) during stable photometric conditions and bracketed by two observations of the CFHTLS-Deep field containing the SNLS tertiary standards.…”
Section: Optical Cfhtls Photometrymentioning
confidence: 99%
“…The colour equations were taken from the Supernova Legacy Survey (Regnault et al 2009). There can be slight shifts of zero points between Megacam system and Sloan photometry, but these zero points vary from field to field, as Fig.…”
Section: Megacam To Sdss Photometric Systemmentioning
confidence: 99%